Granulocyte transfusions for preventing infections in people with neutropenia or neutrophil dysfunction - Estcourt, L; Stanworth, S; Doree, C; Blanco, P; Hopewell, S; Trivella, M; Massey, E (Wiley, 2015)
Despite modern antimicrobials and supportive therapy, bacterial and fungal infections are still major complications in people with prolonged disease-related or therapy-related neutropenia. Since the late 1990s there has been increasing demand for donated granulocyte transfusions to treat or prevent severe infections in people who lack their own functional granulocytes. This is an update of a Cochrane review first published in 2009.To determine the effectiveness and safety of prophylactic granulocyte transfusions compared with a control population not receiving this intervention for preventing all-cause mortality, mortality due to infection, and evidence of infection due to infection or due to any other cause in people with neutropenia or disorders of neutrophil function.We searched for randomised controlled trials (RCTs) and quasi-RCTs in the Cochrane Central Register of Controlled Trials (Cochrane Library 2015, Issue 3), MEDLINE (from 1946), EMBASE (from 1974), CINAHL (from 1937), theTransfusion Evidence Library (from 1980) and ongoing trial databases to April 20 2015.Randomised controlled trials (RCTs) and quasi-RCTs comparing people receiving granulocyte transfusions to prevent the development of infection with a control group receiving no granulocyte transfusions. Neonates are the subject of another Cochrane review and were excluded from this review. There was no restriction by outcomes examined, but this review focuses on mortality, mortality due to infection and adverse events.We used standard methodological procedures expected by The Cochrane Collaboration.Twelve trials met the inclusion criteria. One trial is still ongoing, leaving a total of 11 trials eligible involving 653 participants. These trials were conducted between 1978 and 2006 and enrolled participants from fairly comparable patient populations. None of the studies included people with neutrophil dysfunction. Ten studies included only adults, and two studies included children and adults. Ten of these studies contained separate data for each arm and were able to be critically appraised. One study re-randomised people and therefore quantitative analysis was unable to be performed.Overall, the quality of the evidence was very low to low across different outcomes according to GRADE methodology. This was due to many of the studies being at high risk of bias, and many of the outcome estimates being imprecise.All-cause mortality was reported for nine studies (609 participants). There was no difference in all-cause mortality over 30 days between people receiving prophylactic granulocyte transfusions and those that did not (seven studies; 437 participants; RR 0.92, 95% CI 0.63 to 1.36, very low-quality evidence).Mortality due to infection was reported for seven studies (398 participants). There was no difference in mortality due to infection over 30 days between people receiving prophylactic granulocyte transfusions and those that did not (six studies; 286 participants; RR 0.69, 95% CI 0.33 to 1.44, very low-quality evidence).The number of people with localised or systemic bacterial or fungal infections was reported for nine studies (609 participants). There were differences between the granulocyte dose subgroups (test for subgroup differences P = 0.01). There was no difference in the number of people with infections over 30 days between people receiving prophylactic granulocyte transfusions and those that did not in the low-dose granulocyte group (< 1.0 x 10(10) granulocytes per day) (four studies, 204 participants; RR 0.84, 95% CI 0.58 to 1.20; very low-quality evidence). There was a decreased number of people with infections over 30 days in the people receiving prophylactic granulocyte transfusions in the intermediate-dose granulocyte group (1.0 x 10(10) to 4.0 x 10(10) granulocytes per day) (4 studies; 293 participants; RR 0.40, 95% CI 0.26 to 0.63, low-quality evidence).There was a decreased number of participants with bacteraemia and fungaemia in the participants receiving prophylactic granulocyte transfusions (nine studies; 609 participants; RR 0.45, 95% CI 0.30 to 0.65, low-quality evidence).There was no difference in the number of participants with localised bacterial or fungal infection in the participants receiving prophylactic granulocyte transfusions (six studies; 296 participants; RR 0.75, 95% CI 0.50 to 1.14; very low-quality evidence).Serious adverse events were only reported for participants receiving granulocyte transfusions and donors of granulocyte transfusions.In people who are neutropenic due to myelosuppressive chemotherapy or a haematopoietic stem cell transplant, there is low-grade evidence that prophylactic granulocyte transfusions decrease the risk of bacteraemia or fungaemia. There is low-grade evidence that the effect of prophylactic granulocyte transfusions may be dose-dependent, a dose of at least 10 x 10(10) per day being more effective at decreasing the risk of infection. There is insufficient evidence to determine any difference in mortality rates due to infection, all-cause mortality, or serious adverse events.